Structure Characterization of Four New Sesquiterpene Pyridine Alkaloids from Tripterygium wilfordii Hook. f. and Anti-Inflammatory Activity Evaluations - Yong-Jian Wang; Jian-Gong Yan; Zhong-Mou Zhang; Qiu-Fang Fang; Ya-Dan Wang; Shuang-Cheng Ma (Molecules)
Sesquiterpene pyridine alkaloids (SPAs), as a main class of components in Tripterygium wilfordii Hook. f., possess a variety of bioactivities, such as immunosuppressive, insecticidal, and anti-tumor activities. SPAs can be structurally classed into four subtypes: wilfordate-, evoninate-, iso-wilfordate-, and iso-evoninate types. Our previous study unveiled ten new wilfordate-type SPAs, named wilfordatine A–J, isolated from the roots of Tripterygium wilfordii Hook. f., several of which exhibited significant immunosuppressive activities. As an extension and augmentation of the previous findings, we have now isolated one new iso-wilfordate-type SPA, wilfordatine K (1), alongside three new iso-evoninate-type SPAs, wilfordatines L–N (3–5), and six known analogs. Their structures were characterized by the extensive use of 1D and 2D NMR spectroscopic analysis, as well as HRMS data. Interestingly, compounds 4 and 6 were found to exhibit potent inhibitory effects on the nuclear factor-kappa B (NF-κB) pathway in lipopolysaccharide (LPS)-induced HEK293/NF-κB-Luc cells, with IC50 values of 1.64 μM and 9.05 μM, respectively. Notably, these two compounds had no influence on the cell viability at a concentration of 100 μM. Consequently, they hold significant promise as potential anti-inflammatory candidates for further exploration and development.